The French Invention of Menopause and the Medicalisation of Women's Ageing A History - Downham Moore, Alison M. (Oxford University Press, 2022)
Doctors writing about menopause in France vastly outnumbered those in other cultures throughout the entire nineteenth century. The concept of menopause was invented by Frenchmen medical students in the aftermath of the French Revolution, becoming an important pedagogic topic and a common theme of doctors' professional identities in postrevolutionary biomedicine. Older women were identified as an important patient cohort for the expanding medicalisation of French society and were advised to entrust themselves to the hygienic care of doctors in managing the whole era of life from around and after the final cessation of menses. However, menopause owed much of its conceptual weft to earlier themes of women as the sicker sex, of vitalist crisis, of the vapours, and of astrological climacteric years. This book is the first comprehensive study of the origins of the medical concept of menopause, richly contextualising its role in nineteenth-century French medicine and revealing the complex threads of meaning that informed its invention. It tells a complex story of how women's ageing featured in the demographic revolution in modern science, in the denigration of folk medicine, in the unique French field of hygiène, and in the fixation on women in the emergence of modern psychiatry. It also reveals the nineteenth-century French origins of the still-current medical and alternative-health approaches to women's ageing as something to be managed through gynaecological surgery, hormonal replacement, and lifestyle intervention.